Low doses of cocoa extract supplementation ameliorate diet-induced obesity and insulin resistance in rats. Issue 8 (18th July 2019) - Aranaz, Paula; Romo-Hualde, Ana; Navarro-Herrera, David; Zabala, María; López-Yoldi, Miguel; González-Ferrero, Carolina; Gil, Ana Gloria; Martínez, J. Alfredo; Vizmanos, José Luis; Milagro, Fermín I.; González-Navarro, Carlos J.
Abstract : Supplementation with low doses of a cocoa extract induces metabolic benefits in the prevention of metabolic syndrome in rats, reducing body-weight gain, visceral adiposity and liver steatosis and improving insulin sensitivity and glucose tolerance. Abstract : Cocoa polyphenols exhibit high antioxidant activity and have been proposed as a potential adjuvant for the treatment of metabolic disturbances. Here, we demonstrate that supplementation with low doses (14 and 140 mg per kg per rat) of a complete cocoa extract induces metabolic benefits in a diet-induced obesity (DIO) model of Wistar rats. After 10 weeks, cocoa extract-supplemented animals exhibited significantly lower body weight gain and food efficiency, with no differences in energy intake. Cocoa significantly reduced visceral (epididymal and retroperitoneal) and subcutaneous fat accumulation accompanied by a significant reduction in the adipocyte size, which was mediated by downregulation of the adipocyte-specific genes Cebpa, Fasn and Adipoq . Additionally, cocoa extract supplementation reduced the triacylglycerol/high density lipoprotein (TAG/HDL) ratio, decreased hepatic triglyceride accumulation, improved insulin sensitivity by reducing HOMA-IR, and significantly ameliorated glucose tolerance after an intraperitoneal glucose tolerance test. Finally, no adverse effect was observed in an in vivo toxicity evaluation of our cocoa extract at doses up to 500 mg kg −1 day −1 . Our data demonstrate that low doses of cocoa extract supplementation (14 and 140 mg kg −1 day −1 ) are safe and sufficient to counteract obesity and type-2 diabetes in rats and provide new insights into the potential application of cocoa supplements in the management of the metabolic syndrome.